2017
DOI: 10.1111/ppl.12647
|View full text |Cite
|
Sign up to set email alerts
|

B and E MADS‐box genes determine the perianth formation in Cymbidium goeringii Rchb.f

Abstract: Cymbidium goeringii Rchb.f. is an important ornamental plant with a striking well-differentiated lip. Its complex floral architecture presents an exciting opportunity to examine perianth development. In flowering plants, class A, B and E floral homeotic genes play key roles in the specification of perianth identity. In this study, we used a cDNA library of wild-type C. goeringii flower buds for transcriptome sequencing. Eighteen candidate class A, B and E genes (including AP1/FUL-, AP2-, DEF-, GLO-, SEP- and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…Thus, we isolated two SEP -like genes ( HrSEP-1 and HrSEP-2 ) from wild type H. radiata and analyzed their expression patterns. These genes were expressed in all floral organs of the wild type, matching the expression patterns of other orchid SEP genes from Cymbidium, Oncidium , and Phalaenopsis ( Chang et al, 2009 ; Pan et al, 2014 ; Xiang et al, 2017 ). By contrast, HrSEP-1 transcript was not detected in ‘Ryokusei’, although HrSEP-2 was expressed in all floral organs ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Thus, we isolated two SEP -like genes ( HrSEP-1 and HrSEP-2 ) from wild type H. radiata and analyzed their expression patterns. These genes were expressed in all floral organs of the wild type, matching the expression patterns of other orchid SEP genes from Cymbidium, Oncidium , and Phalaenopsis ( Chang et al, 2009 ; Pan et al, 2014 ; Xiang et al, 2017 ). By contrast, HrSEP-1 transcript was not detected in ‘Ryokusei’, although HrSEP-2 was expressed in all floral organs ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 59%
“…Orchid B-, C/D-, and E-class MADS-box genes have been characterized, and gene duplications in each group have been analyzed ( Tsai and Chen, 2006 ; Aceto and Gaudio, 2011 ; Mondragón-Palomino, 2013 ). To date, several SEP -like genes have been identified from a few orchid species, including AdOM1 in Aranda ( Lu et al, 1993 ), DOMADS1 and DOMADS3 in Dendrobium grex Madame Thong-In ( Yu and Goh, 2000 ), DcOSEP-1 in Dendrobium crumenatum ( Xu et al, 2006 ), OMADS6 and OMADS11 in Oncidium Gower Ramsey ( Chang et al, 2009 ), PeSEP1-4 in Phalaenopsis equestris ( Pan et al, 2014 ) and CgSEP1-4 in Cymbidium goeringii Rchb.f ( Xiang et al, 2017 ). Expression analysis of orchid SEP -like genes showed that SEP3 orthologs ( DOMADS1, DcOSEP1, PeSEP1, PeSEP3 , and OMADS6 ) are expressed in sepals, petals, lips, and columns during flower development, whereas CgSEP1, CgSEP3 , and AdOM1 are rarely expressed in columns ( Lu et al, 1993 ; Xiang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the function of AGL6 orthologs from orchids can be inferred from their expressions. For examples, CgAGL6-1 from C. goeringii has been found to be strongly expressed in the sepals and petals and has been seen to be involved in promoting sepal/petal formation, while CgAGL6-3 from C. goeringii has been found to be highly expressed in the lips and to be involved in lip development [14]. This also provides a clue to understanding the subfunctionalization of AGL6 orthologs following gene duplication events.…”
Section: Discussionmentioning
confidence: 95%
“…For example, EpMADS4 from E. pusilla has been seen to be lowly expressed in the median sepal which has resulted in petaloid sepal appearance, while EpMADS5 from E. pusilla has been observed to be highly expressed in the lips and to be involved in lip development [13]. In addition, CgAGL6-1 from C. goeringii has been found to be strongly expressed in the sepals and petals and to be involved in promoting sepal/petal formation, while CgAGL6-3 from C. goeringii has been seen to be highly expressed in the lips and to be involved in lip development [14]. In asterid eudicots, AGL6 orthologs, such as SlAGL6 from Solanum lycopersicon and PhAGL6 from Petunia hybrida, have been found to be expressed in all floral organs [15,16].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation